Friday

April 18, 2014

April 18, 2014

Posted by **cody** on Friday, March 2, 2012 at 9:50am.

- algebra -
**Dean**, Friday, March 2, 2012 at 12:53pmg(-5)=-4(-5)+3=23

f(23) = -2(23)-7 = -53

(f o g)(-5) = -53

**Related Questions**

Algebra - When Let f (x) = x^2 – 3x + 8 and g(x) = x – 5 Find Find the composite...

college algebra - Let f(x) = square root (x + 2) and g(x) = x^2 − 2. ...

Algebra - Let f(x) = x^2 – 3x + 8 and g(x) = x – 5 (a) Find the sum (f + g)(x) ...

college algebra - Let f(x) = 1/x − 2 and g(x) = 1/x − 3 . Determine ...

calculus - Suppose that f(x)= square root of x and g(x)= 3x-4 and you are asked ...

Math - Domain of Composite function - Find the domain of the composite function ...

Domain of composite function - Can you please help me with the following ...

Algebra - Let f(x) = 6/x-1 and g(x) = 1+3/x. Please fing the composite function...

Domain of composite function - Find the domain of the composite function fog. f(...

Algebra - That is not what the ? is asking. The ? is asking about how to get the...